The politics of imprisonment: how the democratic process shapes the way America punishes offenders - Barker, Vanessa (Studies in crime and public policy, 2009)
The democratic process & imprisonment -- Explaining penal regime variation : political structures & collective agency -- The case of California : neo-populism & retribution -- Washington State deliberates : from fortress prison to de-escalation -- New York : elite pragmatism & managerialism -- Democratic governance, social trust & penal order -- Appendix A: Selected US imprisonment rates, 1971-2006